3-D acoustic homing using 2-D asymptotes. (October 2020) - G.K., Arunkumar; Vachhani, Leena
Abstract: Calling out using sound is a typical means of meeting or knowing where you are with reference to the sound generating source. In acoustic homing, the autonomous vehicle moves to the (home) location where the sound source is placed. This paper attempts to provide a practical solution for acoustic homing of a small-sized autonomous underwater vehicle (AUV). The AUV maneuvers can be easily decoupled in 2-D motions, yaw, and heave, from the rest of the dynamics. Hence, the steering control law is developed based on a simple idea of following in the direction of 2-D asymptote of hyperbola formed by a Time Difference of Arrival (TDOA) measurement. The proposed steering control law is investigated rigorously for 3-D homing. Our main contribution is in designing a simple scheme for steering control substantiated with theoretical analysis, experimental and simulation results. Proposed method orients the AUV in the direction of the acoustic beacon in two stages, coarse and fine, without explicitly localizing the AUV (as in range or bearing based methods) with respect to the home position. The fine steering control law uses TDOA measurements from a single pair of hydrophones avoiding range and bearing computations from measurements. The fine steering is shown to converge the orientation of AUV in the direction towards the location of the acoustic beacon when the initial orientation of AUV is in ( − π ∕ 2, + π ∕ 2 ). The proposed coarse steering law limits the location of the acoustic beacon with respect to the AUV within a region where fine steering is applicable. A placement of sensors is worked out that results in placing the sensors at the corners of a simple rectangular frame. The algorithm is demonstrated using experiments performed on the AUV, Matsya 4.0. Moreover, sensitivity analysis and associated simulation in the Robot Operating System (ROS) demonstrate the robustness of the algorithm against errors in TDOA measurements.